SYNCHROTRON INFRARED AND RAMAN SPECTROSCOPY OF MICRODIAMONDS FROM ERZGEBIRGE, GERMANY - Dobrzhinetskaya L.F.; Zhang J.; Liu Z.; Hemley R.J.; Cartigny P.; Tchkhetia D.; Green II H.W. (My University, 2006)
Metamorphic diamonds from the Erzgebirge, Germany have been investigated using synchrotron infrared absorption, Raman scattering, and fluorescence spectroscopy. Infrared absorption features associated with C-C, C-H bonds, molecular H2O, OH- and CO32- radicals, and N-impurities were observed. The results suggest that a carbon-oxygen-hydrogen (COH) supercritical fluid is the most probable concept to explain the origin of diamonds from ultrahigh-pressure metamorphic terranes (UHPM). Investigation of the nitrogen impurities suggests that the Erzgebirge diamonds belong to the Type 1b-1aA, which is similar to metamorphic diamonds from the Kokchetav massif of Kazakhstan and the Western Gneiss Region of Norway, and differentiates them from other nitrogen-bearing diamonds from kimberlitic sources (Type 1aAB). The occurrence of nitrogen impurities as single atoms in the crystal lattice implies that the Erzgebirge diamonds had a short residence at high-pressure and high-temperature, which therefore suggests a possibility for very fast exhumation. Both infrared and previous studies of nanoinclusions using a transmission electron microscope support a concept of diamond crystallization from a COH rich supercritical fluid. © 2006 Elsevier B.V. All rights reserved.
Keywords: INFRARED; MICRODIAMOND; RAMAN; SYNCHROTRON